PENGARUH MUTU PELAYANAN KEFARMASIAN TERHADAP LOYALITAS PASIEN RAWAT JALAN DI INSTALASI FARMASI RSUD dr. R. SOETIJONO BLORA - Dhevi Novitasari; Ahmad Suriyadi Muslim; Ulviani Yulia Husna (Yayasan Nusantara Hasana Berdikari, 2026)
Pharmaceutical services provided by pharmacists and pharmacy personnel in healthcare facilities must consistently maintain high service quality. In addition to ensuring the safety and effectiveness of therapy, good service quality can enhance patient satisfaction and loyalty. The objective of this study was to determine the effect of the quality of clinical pharmaceutical services on outpatient loyalty at dr. R. Soetijono Regional General Hospital, Blora. This study employed a quantitative design with a cross-sectional approach. The research sample was selected using purposive sampling, with inclusion criteria consisting of outpatients who had received pharmaceutical services at least once. Data were analyzed using the chi-square statistical test to examine the effect of pharmaceutical service quality on patient loyalty. The results from 400 respondents indicated that the overall quality of pharmaceutical services was rated as good by 278 respondents (69.5%), and 303 respondents (75.8%) were categorized as loyal patients. Chi-square analysis yielded a p-value of < 0.001, indicating a significant effect of pharmaceutical service quality on outpatient loyalty at dr. R. Soetijono Regional General Hospital, Blora.